Resistance to carbapenems and other antibiotics in Klebsiella pneumoniae found in seals indicates anthropogenic pollution. (23rd April 2020) - Duff, James Paul; AbuOun, Manal; Bexton, Steve; Rogers, Jon; Turton, Jane; Woodford, Neil; Irvine, Richard; Anjum, Muna; Teale, Christopher
Abstract : Background: The beta‐lactamase enzyme OXA‐48 has spread widely in recent years in Enterobacteriaceae associated with man, disseminated primarily on incompatibility group L/M plasmids. OXA‐48 confers resistance to carbapenems, important antimicrobials for treating highly resistant bacterial infections in humans. This enzyme has rarely been detected in bacteria from animals. Furthermore, the use of carbapenem compounds is not permitted in food‐producing animals in Europe and to our knowledge has not been reported in food‐producing animals globally. Methods: Bacterial isolates from lesions in stranded, free‐living, juvenile common seals ( Phoca vitulina ) were identified. Antimicrobial susceptibility testing and whole genome sequencing analysis were used to characterise antimicrobial resistance genes carried by the bacteria. Results: Here, we report the detection of Klebsiella pneumoniae subspecies pneumoniae carrying the bla OXA‐48 gene on an incompatibility group L/M plasmid from an infection in a common seal. Conclusion: Evidence is accruing that marine mammals may be infected with bacteria originating from anthropogenic sources, such as human sewage, contaminating the environment.